Biodiversity values of small headwater streams in contrasting land uses in the Auckland region - RG Storey; S Parkyn; MW Neale; T Wilding; G Croker (New Zealand Journal of Marine and Freshwater Research, 2011)
The biodiversity values of 12 small headwater streams (catchments mostly

Life histories and life history strategies of invertebrates inhabiting intermittent streams in Hawke's Bay, New Zealand - RG Storey; JM Quinn (New Zealand Journal of Marine and Freshwater Research, 2011)
Intermittent streams are predicted to harbour macroinvertebrate taxa with particular life history traits that allow them to complete development in a limited time and survive periods without water. Three intermittent headwater streams in Hawke's Bay, New Zealand, had more taxa with very small body size, plurivoltine life cycles, low dissemination potential, long‐lived adults and asexual reproduction than three nearby perennial streams. We traced the population size structure and adult flight periods of six aquatic insect taxa, and the population size structure of an aquatic snail, in three intermittent streams to provide basic information on larval growth rates and infer whether they use particular life history stages to survive summer drought. The insect taxa appeared to over‐summer primarily as eggs, whereas the snail Potamopyrgus antipodarum over‐summered at various stages of maturity. Final instar larvae and adults of most insect taxa appeared well ahead of stream drying, suggesting they can survive early‐onset drought. However, late‐onset drought would allow more larvae to complete development.